Regionalista z pasją dalekich podróży, czyli Filip Sulimierski i jego „Wędrowiec” - Domarańczyk, Daria (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The article focuses on an outstanding Polish publisher and ethnographer – Philip Sulimierski (1843–1885). Although trained as a mathematician, he was a traveler at heart and edited the magazine “Wędrowiec”. It was the first illustrated tourism and travel magazine in Poland. This 19th century-magazine was so original for its time that the format of “National Geographic” was based on it. Sulimierski was also the creator and editor of the “Dictionary of the Polish Kingdom and other Slavic Countries”, which to this day remains an invaluable resource for geographers, ethnologists and historians.